2010
DOI: 10.1128/aem.03059-09
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Affinity Immunochromatography Column-Based Tests for Sensitive Detection of Clostridium botulinum Neurotoxins and Escherichia coli O157

Abstract: Existing methods for detection of food-borne pathogens and their toxins are frequently time-consuming, require specialized equipment, and involve lengthy culture procedures and/or animal testing and are thus unsuitable for a rapid response to an emergency public health situation. A series of simple and rapid affinity immunochromatography column (AICC) assays were developed to detect Clostridium botulinum neurotoxin types A, B, E, and F and Escherichia coli O157 in food matrices. Specifically, for milk, grape j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Optimally, ELISAs based on mAb have to be tested against all the different subtypes of a given serotype. Indeed, a variation or lack in recognition of a certain subtype has been observed for some mAb and mAb-based ELISAs (Gibson et al 1987(Gibson et al , 1988Smith et al 2005;Kalb et al 2009Kalb et al , 2011bBrunt et al 2010).…”
Section: Selected Examples Of Different Elisa Formatsmentioning
confidence: 99%
See 2 more Smart Citations
“…Optimally, ELISAs based on mAb have to be tested against all the different subtypes of a given serotype. Indeed, a variation or lack in recognition of a certain subtype has been observed for some mAb and mAb-based ELISAs (Gibson et al 1987(Gibson et al , 1988Smith et al 2005;Kalb et al 2009Kalb et al , 2011bBrunt et al 2010).…”
Section: Selected Examples Of Different Elisa Formatsmentioning
confidence: 99%
“…This problem is usually less pronounced with pAb recognizing numerous epitopes on a target protein, but also pAb have been shown to neutralize BoNT subtypes differently (Kozaki et al 1977) or in extreme fail to recognize a certain subtype: Brunt and colleagues showed that a particular pAb directed against BoNT/F1 failed to recognize culture supernatants of a nonproteolytic F strain (Brunt et al 2010). Notably, the highest divergence among the subtypes is found in BoNT/F (36 %) (Raphael et al 2010a).…”
Section: Selected Examples Of Different Elisa Formatsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, Brunt and colleagues (Brunt, Webb, and Peck, 2010) have developed a number of rapid affinity immunochromatography column (AICC) assays for the detection of BoNT serotypes A, B, E, and F in food matrices. These authors reported a detection limit for BoNT/A of 0.5 ng, two fold more sensitive than earlier reported lateral flow methods.…”
Section: Affinity Immunochromatography Column-based Methodsmentioning
confidence: 99%
“…Recently, alternative rapid methods, such as quantitative real-time PCR assays, have been developed for the detection of C. botulinum (Kirchner et al 2010;Satterfield et al 2010). Brunt et al (2010) developed a sensitive and rapid immunochromatography column-based test for the detection of BoNTs. Fig.…”
Section: Electrochemical Detection Of Botulinum Neurotoxins (Bonts)mentioning
confidence: 99%